CONDITION OF INCIDENCE AND EPIDEMIC SITUATION ON SYPHILIS IN AZERBAIJAN - Akhmedova, R.M. (World of Medicine and Biology, 2013)
From 2000 for 2011 intensity of epidemic process of syphilis among the population of the Republic Azerbaijan continued to remain high, reaching peak in 2000 and 2011. This phenomenon is connected with population shift, an urbanization, deterioration of material security of the population, shortcomings of the organization of сliniс-laboratory inspection and therapy of patients by this disease. The provided data showed need of careful complex сliniс-laboratory inspection of the patients addressing in skin and venereologic and other treatment-and-prophylactic establishments with application of methods of the immunofermental analysis and its options with quantitative definition of antibodies to causative agents of syphilis.
Keywords: syphilis; algorithm of the inspection; the mixed syphilitic infection